النظرية المعجمية العربية - Bisri Mustofa (LISANIYAT, 2010)
As one of the biggest language in the world, Arabic has several objects of studies. Mu’jam theory is one of the objects of studies. Arabic Mu’jam theory has risen since earlier of Islam development, exactly at the first hijriyah century. The signed of the theory is Mu’jam  al- ‘ain. The first Arabic Mu’jam based on Makharij al-Huruf al-Hija’iy by al-Khalil Ibn Ahmad al- Farahidy al-Mishry. He was an Linguist of Islamic Arabic (100 – 175 H).Keyword: Language, Arabic.